2017
DOI: 10.1016/j.scijus.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The transfer of diatoms from freshwater to footwear materials: An experimental study assessing transfer, persistence, and extraction methods for forensic reconstruction

Abstract: In recent years there has been growing interest in environmental forms of trace evidence, and ecological trace evidence collected from footwear has proved valuable within casework. Simultaneously, there has been growing awareness of the need for empirical experimentation to underpin forensic inferences. Diatoms are unicellular algae, and each cell (or 'frustule') consists of two valves which are made of silica, a robust material that favours their preservation both in sediments and within forensic scenarios. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 50 publications
5
29
0
Order By: Relevance
“…Diatom analysis used in this manner is relatively recent, with the potential to offer valuable environmental and circumstantial intelligence during crime reconstructions. A limited number of empirical research studies have previously considered diatom transfer from freshwater and terrestrial environments onto clothing and footwear materials, and the methods appropriate for their collection and analysis [15,[20][21][22]. Despite this initial focus, additional research is required to investigate the transfer and persistence dynamics of diatoms in experimental scenarios pertinent to forensic casework.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…Diatom analysis used in this manner is relatively recent, with the potential to offer valuable environmental and circumstantial intelligence during crime reconstructions. A limited number of empirical research studies have previously considered diatom transfer from freshwater and terrestrial environments onto clothing and footwear materials, and the methods appropriate for their collection and analysis [15,[20][21][22]. Despite this initial focus, additional research is required to investigate the transfer and persistence dynamics of diatoms in experimental scenarios pertinent to forensic casework.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…An initial study by Scott et al [15], found that diatoms transferred to new/used 100% cotton clothing surfaces following different periods of contact (3 minutes to 24 hours) with freshwater and soil environments. Furthermore, Levin et al [21] examined freshwater diatom transfer to five different footwear materials (soles and uppers) following three immersion intervals (30 seconds to 30 minutes). Though both studies identified the diatoms present by morphology or by genus, neither considered the potential influence of particulate variability on diatom transfer to clothing.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical studies addressing the transfer and persistence of trace materials have developed since the early work of Pounds and Smalldon () (fibers), Brewster, Thorpe, Gettinby, and Caddy () and Hicks, Vanina, and Margot () (glass), and Morgan et al () and Bull, Morgan, Sagovsky, and Hughes () (general particulates). There is now a growing body of published work that addresses a wide range of different physical traces (Bitter, (smoke residues), Maitre et al, (GSRs), Palmer, Sheridan, Puckett, Richardson, & Lo, and Slot et al, (fibers), Levin, Morgan, Scott, & Jones, (diatoms), Morgan, Scott, Ainley, & Bull, (soils) Morgan, Flynn, et al, , and Morgan, Allen, King, & Bull, (pollen)).…”
Section: Understanding Trace Materialsmentioning
confidence: 99%